Kandungan Bahan Organik Total (BOT) dan Kekeruhan pada Air di Estuari DAM, Badung, Bali - Ahmad Alfian Rahman; Ima Yudha Perwira; I Wayan Darya Kartika (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2022)
This study aimed to know the Total Organic Matter (TOM) of water and the water quality in the Estuary DAM, Badung, Bali. This study was carried out for 1 month along March of 2021. Water samples were collected from 4 stations representing: the inlet (station 1), the middle part (station 2 and 3), and the outlet (station 4). The TOM of water was measured using Permanganate Test titrimetrically. Dissolved Oxygen (DO), pH and water turbidity were measured using: DO meter, pH meter, and Turbidimeter. Result of the study showed that the TOM of water in the Estuary DAM was ranging from 1,8 to 13,9 mg/L. The TOM of water at Week 2 and 4 was relatively low compared to other period which might be caused by dilution regarding to the high rainfall in this period. The DO level was ranging from 4,0 to 6,5 mg/L, pH was ranging from 6,0 to 6,2, and turbidity was ranging from 3,73 to 13,82 mg/L